COMMODITY SCIENCE AS A PREDECESSOR OF QUALITY MANAGEMENT SCIENCES - Ruževičius, Juozas (Ekonomika, 2010)
In this study, the evolution, content, trends and perspective of commodity science as a predecessor of quality management sciences and as an education subject are analyzed. The new models of the interface of commodity science with other disciplines, of the coverage of contemporary quality sciences and of quality management development stages are presented. Also, analysed are the aspects of quality experts’ and quality managers’ formation at Lithuanian universities, business schools and colleges. The article was written using scientific, normative and legal literature, systemising the good practices of Western universities, commodity and quality related international organisations and the results of author’s systematic researches of commodities and services quality problems. The author formulates the insights for the future development of commodity science and quality management as a subject of science and education.